Anatomy as Art of Dis-deception: The Moral Anatomies of Alessandro Tommaso Arcudi and Ottavio Scarlattini - Iaccarino, Imma (Intermédialités / Intermediality, 2023)
This article aims to investigate a relevant but still little-explored function of cadaveric dissection, a medical procedure that in the early modern age offers itself as the most effective tool for unmasking deception and restoring a regime of authenticity and transparency. In this period, anatomy, perceived as capable of revealing layer by layer the physical and spiritual impostures of human nature, proves particularly useful against behavioural practices of simulation and dissimulation, and especially in countering the social phenomenon of religious dis/simulation (also referred to as “hypocrisy” by early moderns). This moralized conception of anatomy underlies two Italian works published at the end of the seventeenth century: the encyclopaedic and anatomical illustrated atlas L’huomo, e sue parti figurato (1684) by Ottavio Scarlattini (1623–1699) and the moral treatise Anatomia degl’Ipocriti (1699) by Dominican Alessandro Tommaso Arcudi (1655–1718). Both symbolically use dissection as a pharmakon to detect and cure hypocrisy in others and in oneself. In Scarlattini’s case, the metaphorical exposition of human interiority through dissection is also visually represented in a substantial iconographic apparatus in which the debate between masquerade and transparency appears polarized in organic sites, such as the heart and the mouth, symbols of truth and fraud, respectively.